(State) empathy: how context matters - Katrin Heyers; Katrin Heyers; Robin Schrödter; Lena Sophie Pfeifer; Sebastian Ocklenburg; Sebastian Ocklenburg; Sebastian Ocklenburg; Onur Güntürkün; Ursula Stockhorst (Frontiers in Psychology)
Empathy is a pivotal capacity that is essential for human interaction. It encompasses cognitive empathy, which is the ability to understand another individual’s emotional state, and affective empathy, which is to express an appropriate affective response to another person’s emotional state. Recent advancements in empathy research have highlighted the contextual nature of both cognitive and affective empathy, signifying their susceptibility to modulation by situational factors. Despite this progress, a comprehensive mechanistic understanding of empathy as a form of situated cognition that integrates both state and trait dimensions remains scarce. This review outlines the interplay of trait and state empathy and how state empathy emerges from a dynamic interplay between bottom-up processes and top-down control mechanisms. It further covers which situational factors increase versus decrease state empathy. In addition, to assist in selecting appropriate measurement tools for measuring trait and/or state empathy, the review categorizes existing empathy measurement instruments. Taken together, this review provides a roadmap for enhancing the efficacy of future empathy studies by: (1) outlining the current theoretical and methodological considerations for disentangling trait and state empathy; (2) organizing existing empathy measurement tools to aid researchers in selecting appropriate tools for future studies; (3) describing the interplay between bottom-up processes and top-down control mechanisms for state and trait empathy; and (4) reviewing factors that increase or decrease state empathy to prevent their potential interference and enable a more accurate assessment of empathy.